Gut Mycobiome in Patients With Chronic Kidney Disease Was Altered and Associated With Immunological Profiles - Hu, Jialin; Wei, Shichao; Gu, Yifeng; Wang, Yang; Feng, Yangkun; Sheng, Jiayi; Hu, Lei; Gu, Chaoqun; Jiang, Peng; Tian, Yu; Guo, Wei; Lv, Longxian; et al. (Frontiers in Immunology, 2022)
Objectives Mounting evidence suggests bacterial dysbiosis and immunity disorder are associated with patients with chronic kidney disease (CKD). Recent studies of fungi in human microbiome surveys have revealed that microbiome signatures linked to health. We aim to characterize the profile of fungal microbiome in the gut of CKD patients and its correlation to serum immunological profiles. Methods and materials Ninety-two CKD patients and gender-age-BMI matched healthy controls (HC) were recruited. Fresh samples were collected using sterile containers. ITS ribosomal RNA gene sequencing was performed on the samples. An immunoturbidimetric test was used to assess serum levels of immunological features. Results The CKD cohort displayed a different microbial community from that in HC cohort according to PCoA (P=0.001). The CKD cohort showed higher levels of microbial richness and diversity comparing to HC (P<0.05). The CKD cohort had lower abundances of Candida, Bjerkandera, Rhodotorula and Ganoderma comparing to HC cohort, while had higher Saccharomyces (P<0.05). However, the microbial community alteration was inconsistent with the severity of kidney damage in patients, as only patients in CKD stage 1~3 had differed microbial community with respect to HC based on PCoA (P<0.05). Several CKD enriched genera were positively or negatively associated with the CKD enriched serum immunological factors, such as Saccharomyces and Ganoderma were positively or negatively associated with serum κ light chain, respectively (P<0.05). Conclusions Not only alterations were revealed in CKD patients, but also the dysbiosis was associated with immunological disorder. These findings suggest microbial modulation in CKD should target to fungal disorder.